Alcohol Consumption and Road Rage among Commercial Tricycle Riders in South-South, Nigeria - Ayinmoro, Aboluwaji D.; Uzobo, Endurance; Tobin, Violet D.; Owota, Kenibolayefa M. (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
This study examines the relationship between alcohol consumption and road rage experience among commercial tricycle riders in south-south Nigeria. Using expectancy theory of motivation as theoretical framework, a sample of 360 subjects was selected in a multi-stage sampling technique utilizing a structured questionnaire to elicit information about socio-demographic variables, alcohol consumption and road rage. Descriptive statistics and multiple regressions were used as method of data analysis at 0.01 and 0.05 significance level. The results showed that commercial tricycle riders were dominated by males and those who had attained secondary school education. It was further revealed that respondents consumed palm wine, spirit, beer, Goldberger, Gulder, stout, wine and Ogogoro at least once in a week. Other intoxicant substances that were consumed by respondents included marijuana, cannabis, cocaine, cigarettes, tobacco and tobacco snuffing. Further findings revealed that there is significant relationship between alcohol consumption and road rage especially for spirit (OR = 0.158, p<0.01) and Ogogoro (OR = 0.116, p<0.01) consumption. Association also exists between road rage and road traffic crashes. The study concluded that riding tricycle under the influence of alcohol consumption should be discouraged through policy formulation in order to curb the perpetration of road rage and road traffic crashes in the country. Keywords: Alcohol use, road rage, road crash, commercial tricycle riders, Nigeria